Entrepreneur in business environment scarcity - Mandysová, Ivana; Valentová, Lucie (SGEM, 2017)
Entrepreneurs have proved flexibility in counteracting scarcity of the business environment and grasping opportunities. Anyway, the public policy should help entrepreneurs by providing public goods and by creating a relevant environment for them. To overcome environment scarcity and to create a dynamic economy, which ensures that entrepreneurs can start and develop their businesses, public policy should understand entrepreneurship, support it and motivate it properly.
Podnikatel v nepříznivém podnikatelském prostředí
Keywords: entrepreneur; business environment; scarcity; podnikatel; podnikatelské prostředí; nepříznivé podnikatelské prostředí